SIKAP PENGARANG DALAM NOVEL PALAWIDJA KARYA KARIM HALIM DAN KEMBANG JEPUN KARYA REMY SILADO: SEBUAH BANDINGAN - Bahtiar, Ahmad (Adabiyyāt: Jurnal Bahasa dan Sastra, 2015)
This research aims at scrutinizing two novels, Palawidja by Karim Halim dan Kembang Jepun by Remy Sylado, by using the theory of literary sosiology to observe the point of views of each authors. Obviosly, they have different pictures on the situation in Indonesia during the Japanese occupation.  Remy Sylado, who wrote  after the Japanese occupation,  gives a more objective picture in his novels than Karim Halim, who live and wrote novels during the Japanese occupation, does. Palawidja is biased due to the fact that Karim Halim worked for Balai Pustaka, a publishing company under the control of the Japanese authority. Therefore, he supported the Japanese propaganda and could not give an objective picture of the condition in Indonesia at the time.